The Establishment of Marine Protected Areas Beyond National Jurisdiction: The Central Arctic Ocean - Sjögren, Sofia (UiT Norges arktiske universitet, 2016)
The thesis presents and analyses the legal basis for the establishment of MPAs under the United Nations Convention on the Law of the Sea and its potential Implementing Agreement on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction. Springing from this, the thesis discusses the issue of competence for the establishment of MPAs respecting parts of the Central Arctic Ocean.